2019
DOI: 10.1159/000504766
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hyaluronic Acid on Traumatic Urethral Inflammation

Abstract: Purpose: This study investigated the possible beneficial effect of hyaluronic acid (HA) on traumatic urethral healing. Methods: A total of 40 adult male Wistar rats were randomized into four groups: control, sham (serum physiologic; SF group), HA 1.8%, and HA 3%. A tiny hook was introduced and drawn at the 12 o'clock position into the urethra for the SF and HA groups to create a urethral inflammation model. Either SF or HA was applied intraurethrally for 5 consecutive days. After a 15-day follow-up period (21s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Daily application of erythropoietin (EPO) or a single injection with botulinum toxin-A in urethral mucosa caused decrease in urethral fibrosis, with no increasing effect in high dosage EPO animals [ 29 , 30 ]. Both low and high dose daily application of sodium hyaluronate (5 days total) decreased urethral tissue thickness after 21 days [ 31 ]. Lastly, daily use of a calcium antagonist, diltiazem, for 5 days did not result in any significant histopathological changes after 21 days (connective tissue thickness, epithelial lining and degree of inflammation) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Daily application of erythropoietin (EPO) or a single injection with botulinum toxin-A in urethral mucosa caused decrease in urethral fibrosis, with no increasing effect in high dosage EPO animals [ 29 , 30 ]. Both low and high dose daily application of sodium hyaluronate (5 days total) decreased urethral tissue thickness after 21 days [ 31 ]. Lastly, daily use of a calcium antagonist, diltiazem, for 5 days did not result in any significant histopathological changes after 21 days (connective tissue thickness, epithelial lining and degree of inflammation) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Italiano et al 23 demonstrated preservation of the urethral lumen with adequate compliance by resecting the urethra and replacing a segment with biodegradable hyaluronate-based grafts. Yıldızhan et al 24 evaluated the effect of HA on traumatic wounds to the urethra of 40 male Wistar rats. The results were not statistically significant, probably because of the short evaluation time, but a significant increase in tissue thickness was observed in the control group treated with saline.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“… 1 Untreated urethral stricture can lead to life-threatening complications including urinary tract infection (UTI), acute urinary retention, hydronephrosis, and periurethral abscess. 2 , 3 The prevalence of urethral stricture is 0.2%-0.6%. 2 Urethral stricture can be treated with endoscopic or open (conventional) surgeries.…”
Section: Introductionmentioning
confidence: 99%